Intensitas Nyeri Punggung Bawah Ibu Hamil Trimester III yang Melakukan Prenatal Yoga - Putu Dyah Pramesti Cahyani; Ni Gusti Kompiang Sriasih; Made Widhi Gunapria Darmapatni (Poltekkes Kemenkes Padang, 2020)
Low back pain is musculoscletal problem that causes discomfort during pregnancy. Prenatal yoga is non-pharmacology method that can reduce low back pain. This research aims to find the low back pain difference of third trimester pregnant mothers before and after having prenatal yoga in Bunda Setia clinic. This is pre-experimental research with one group pre-test post-test research design. The samples are 36 third trimester pregnant mothers with gestational age of 36-38 weeks who join prenatal yoga in Bunda Setia clinic, chosen by consecutive sampling. The data are taken by observing the level of lower back pain before and after having prenatal yoga. The respondents have prenatal yoga once a week for 2 weeks, 60 minutes duration. The bivariate analysis uses Wilcoxon test α < 0,05. The median of low back pain before prenatal yoga is 5, after prenatal yoga reduce to 2 with ρ value = 0,000 < α (0,05) and Z value (-5.233). The conclusion shows there is low back pain level difference of third trimester pregnant mothers before and after having prenatal yoga in Bunda Setia clinic. This intervention is suggested to be applied by medical staff in order to resolve low back pain of pregnant mothers.